Characterization of TERT and BRAF copy number variation in papillary thyroid carcinoma: An analysis of the cancer genome atlas study. Issue 6 (18th December 2020) - McKelvey, Brittany A.; Zeiger, Martha A.; Umbricht, Christopher B.
Abstract: Alterations in the genome, including mutations and copy number variation (CNV), can drive cancer progression. The Cancer Genome Atlas (TCGA) project studying papillary thyroid cancer (PTC) identified a number of recurrent arm‐level copy number amplifications, some spanning genes that are also commonly mutated in thyroid cancer. Herein, we focus on the role of TERT and BRAF CNV in PTC, including its relation to mutation status, gene expression, and clinicopathological characteristics. Utilizing TCGA CNV data, we identified focal amplifications and deletions involving the TERT and BRAF loci. TERT amplifications are more frequent in later stage thyroid tumors; in contrast, BRAF amplifications are not associated with stage. Furthermore, TERT amplifications are more frequently found in tumors also harboring TERT mutations, the combination further increasing TERT expression. Conversely, BRAF amplifications are more frequently found in BRAF wildtype tumors, and are more common in the follicular subtype of PTC as well as classic PTCs associated with a high follicular component and a RAS‐like expression profile (assessed by the BRAF/RAS score). This is the first study to examine the TCGA thyroid dataset for gene‐level CNV of TERT and BRAF, and their relationship with mutation status, tumor type and tumor stage. Assessing the differences in patterns of TERT and BRAF amplifications in the context of the mutation status of these genes may provide insight into the differing roles CNV can play depending on tumor type, and may lead to a better understanding of cancer drivers in thyroid cancer.